Energy consumption in hotel industry : case study in Ohrid - Petrovska Reckoska, Gordana (Array, 2008)
Abstract: Renewable energy is necessary for each industry functioning, also for hotel industry. It's necessary for warming, lightening hotels, for kitchens functioning in hotels, for transport vehicles movement, for hotel pools, etc. In lack of classic energy sources, long period of time some work is done on finding new energy sources, besides oil and coal, water and wind. Nowadays, solar energy is very popular, which is already supplied, bio-energy, wind energy, water energy, geothermal and gas energy, steam, and still a work is done on permanent finding of new renewable energy sources (fuel cell resources, ocean/wave resources). In this paper, overworked data is shown, brought by Ohrid hotels and SWOT analyses has been done of energy consumption in hotel industry in Ohrid, with proposals for modernization, efficiency, aiming to modern tourism development, environment protection, human health protection. In this way, basic demands for entering the European Union will be satisfied and legislative harmonization in Republic of Macedonia with other EU members is going to be realized